Effective Application of 4th Industrial Revolution Technologies During Engineering Research and Teaching in Ugandan Universities - Isaac, Ndawula; Dianah, Asiimwe; Samuel, S. Mushakangoma; Pascal Musaazi, Senkindu (The 2nd Annual Higher Education Conference, Hotel Africana Kampala, Uganda, 2020)
The 4th Industrial Revolution (4IR) technologies is the recent research topic of interest among the academicians, since the 4IR technologies make up the latest era of digitization. The 4IR technologies demands changes in the three fundamental functions (teaching, research and community service) of higher institutions of learning. Each revolution technologies needs different job skills and competences, the 4IR technologies will also require new job skills and competences from the university graduates particularly in the field of engineering. The teaching staff at universities shall play an important role in imparting the necessary job skills and competences to graduates. Recently several research on 4IR technologies in higher institutions of learning has been presented, but none is addressing the issue of availability of effective utilization of 4IR technologies in engineering education. So, this paper presents the investigation of the availability of effective application of 4IR technologies during university engineering research and teaching in Ugandan universities. The paper also examined the behavior, knowledge, and perception of teaching staff towards 4IR technologies in the university engineering education in Uganda. 256 respondents were interviewed using online questionnaire and data collected was analyzed using MATLAB program. The findings disclose that there is low degree of application of 4IR technologies by teaching staff in engineering sector during teaching and research in the seven universities in Uganda.